2007
DOI: 10.1562/0031-8655(2000)0720477faoduf2.0.co2
|View full text |Cite
|
Sign up to set email alerts
|

Fluorometric Analysis of DNA Unwinding (FADU) as a Method for Detecting Repair-induced DNA Strand Breaks in UV-irradiated Mammalian Cells¶

Abstract: Fluorometric analysis of DNA unwinding (FADU assay) was originally designed to detect X‐ray–induced DNA damage in repair‐proficient and repair‐deficient mammalian cell lines. The method was modified and applied to detect DNA strand breaks in Chinese hamster ovary (CHO) cells exposed to ionizing radiation as well as to UV light. Exposed cells were allowed to repair damaged DNA by incubation for up to 1 h after exposure under standard growth conditions in the presence and in the absence of the DNA synthesis inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Thus, more detailed studies are necessary to establish whether cell damage induced by UV radiation is apoptotic or non-apoptotic. The measurement of condensed pycnotic nuclei from Hoechst 33342 fluorescent micrographs has been used in in vitro photocytotoxicity studies of rat hepatocytes, Chinese hamster ovary cells, Xenopus XTC-2 cells, and B-cell hybridoma [50][51][52][53]. Findings from these studies support the use of Hoechst 33342 as a sensitive nuclui morphological marker for monitoring UV-induced cell damage.…”
Section: Discussionmentioning
confidence: 92%
“…Thus, more detailed studies are necessary to establish whether cell damage induced by UV radiation is apoptotic or non-apoptotic. The measurement of condensed pycnotic nuclei from Hoechst 33342 fluorescent micrographs has been used in in vitro photocytotoxicity studies of rat hepatocytes, Chinese hamster ovary cells, Xenopus XTC-2 cells, and B-cell hybridoma [50][51][52][53]. Findings from these studies support the use of Hoechst 33342 as a sensitive nuclui morphological marker for monitoring UV-induced cell damage.…”
Section: Discussionmentioning
confidence: 92%
“…Results of mass spectrometry analysis are provided in Table 1 and Total ion chromatogram of rasayana injection is provided as supplementary figure 1S. proportional to DNA strand breaks and inversely proportional to the strand breaks repair (Baumstark- Khan et al, 2000). The initial kinetic studies have shown that the exposure of PBMCs of aged (55 -80.years; N= 16) and young (22 -25 years; N=16) subjects with 1 J/cm 2 of UVC resulted in an increase in the strand breaks up to 3 h repair time.…”
Section: Resultsmentioning
confidence: 99%
“…Exposure to UVB (28-315 nm) induces CPD and 6-4PP photolesions (36,37). These premutagenic DNA lesions are shown to be detrimental to replication, capable of causing replication fork collapse (38)(39)(40). In this study, we investigated the DSB repair kinetics by visualizing 53BP1 foci in melanoma Figure 6.…”
Section: Discussionmentioning
confidence: 99%